COMPANY SIZE AS A MODERATION VARIABLE OF SHARIA COMPLIANCE AND GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE (Study on Sharia Commercial Banks 2016-2021) - Islamiah, Cahyani; Mashudi, Mashudi; Asiyah, Binti Nur (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study is to examine The Influence of Sharia Compliance and Good Corporate Governance on the Financial Performance of Islamic Banks with Company Size as a Moderating Variable (Studies on Islamic Commercial Banks 2016-2021. Quantitative approach with Islamic Commercial Banks in Indonesia as a research object. A total of 48 samples originating from annual financial reports from 2016-2021 are used as a reference in processing data with the help of E-views 9 Software. The results showed that: Islamic Income Ratio and Profit Sharing Ratio variables partially have a positive and significant effect on financial performance. The Islamic Investment Ratio variable has no significant effect on the Bank's Financial Performance. Simultaneously the variables Islamic Income Ratio, Profit Sharing Ratio, Islamic Investment Ratio, Good Corporate Governance together will improve the Bank's Financial Performance. Islamic Income Ratio, Islamic Investment Ratio and Good Corporate Governance variables which are moderated by company size do not affect the financial performance of Islamic commercial banks. Meanwhile, the Variable Profit Sharing Ratio, which is moderated by company size, has an effect on the financial performance of Islamic commercial banks. Keywords: Sharia Compliance, Good Corporate Governance, Financial Performance of Islamic Banks, and Company Size